2005
DOI: 10.1108/14635770510600375
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking culture and performance in Chinese organizations

Abstract: PurposeTo show differences in organizational performance, management style and systems, resulting from cultural differences in three organizational types: foreign‐owned, joint ventures, and Chinese‐owned and operated.Design/methodology/approachA survey method was used to assess the management systems, leadership and styles within the cultural contexts of the three types of organizations using Hofstede's four cultural dimensions. Organizational performance was measured using balanced scorecard method and factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 30 publications
1
45
0
2
Order By: Relevance
“…For example, benchmarking with China has been researched by Garg and Ma [18] and Li-Hua and Simon [19]. Many of these articles show the speed by which Asian companies are gaining on their Western competitors.…”
Section: Definitonsmentioning
confidence: 97%
“…For example, benchmarking with China has been researched by Garg and Ma [18] and Li-Hua and Simon [19]. Many of these articles show the speed by which Asian companies are gaining on their Western competitors.…”
Section: Definitonsmentioning
confidence: 97%
“…Nonetheless, [109] claimed that financial measures of performance only capture one part of organizational performance. This is supported by [110] who advocated the movement toward recognizing non-financial measures, given that they focus on a firm's long-term success [27]. Non-financial performance relates to the organization's effective marketing activities and can be evaluated through customer loyalty, customer satisfaction, market share, quality, new product development, and so on [3] and [111].…”
Section: Organizational Performancementioning
confidence: 99%
“…In an interesting investigation of the use of benchmarking by foreign owned, joint venture and Chinese owned and operated firms in China, Garg and Ma (2005) concluded that process performance goals (e.g. ISO 90002) and employee competency (in key information systems and technologies) were perceived to be critical elements of employee and firm performance and that foreign owned operations and joint ventures were more comfortable with their ability to focus successfully on these performance measures than their Chinese owned and operated counterparts.…”
Section: Systems Designmentioning
confidence: 99%